Active Learning Pedagogies in High School and Undergraduate STEM Education - Rea Lavi; Lykke Brogaard Bertel (MDPI AG, 2024)
Active learning (AL) typically involves (1) students applying knowledge and higher-order thinking (2) individually and in groups to (3) problems, cases, scenarios, or questions while (4) reflecting on their learning [...]